Facial Soft Tissue Thickness (Fstt) And Its Sexual Dimorphism In A Malaysian Sample: A Ct-Based Approach - Muhammad Faiz Mohd Fauad; Aspalilah Alias; Ker Woon Choy; Helmi Mohd Hadi Pritam; Eric Chung; Ng Wei Lin; Arofi Kurniawan; Khalid Ayidh Alqahtani; Nur Azwa Syuhada Samshuddin (USIM Press, 2026)
Non-Indexed Publication